Laboratory Methods for Detection of Infectious Agents and Serological Response in Humans With Tick-Borne Infections: A Systematic Review of Evaluations Based on Clinical Patient Samples - Henningsson, Anna J.; Aase, Audun; Bavelaar, Herjan; Flottorp, Signe; Forsberg, Pia; Kirkehei, Ingvild; Lövmar, Matilda; Nilsson, Kenneth; Nyman, Dag; Ornstein, Katharina; Sjöwall, Johanna; Skogman, Barbro H.; et al. (Frontiers in Public Health, 2021)
Background: For the most important and well-known infections spread by Ixodes ticks, Lyme borreliosis (LB) and tick-borne encephalitis (TBE), there are recommendations for diagnosis and management available from several health authorities and professional medical networks. However, other tick-borne microorganisms with potential to cause human disease are less known and clear recommendations on diagnosis and management are scarce. Therefore, we performed a systematic review of published studies and reviews focusing on evaluation of laboratory methods for clinical diagnosis of human tick-borne diseases (TBDs), other than acute LB and TBE. The specific aim was to evaluate the scientific support for laboratory diagnosis of human granulocytic anaplasmosis, rickettsiosis, neoehrlichiosis, babesiosis, hard tick relapsing fever, tularemia and bartonellosis, as well as tick-borne co-infections and persistent LB in spite of recommended standard antibiotic treatment. Methods: We performed a systematic literature search in eleven databases for research published from 2007 through 2017, and categorized potentially relevant references according to the predefined infections and study design. An expert group assessed the relevance and eligibility and reviewed the articles according to the QUADAS (diagnostic studies) or AMSTAR (systematic reviews) protocols, respectively. Clinical evaluations of one or several diagnostic tests and systematic reviews were included. Case reports, non-human studies and articles published in other languages than English were excluded. Results: A total of 48 studies fulfilled the inclusion criteria for evaluation. The majority of these studies were based on small sample sizes. There were no eligible studies for evaluation of tick-borne co-infections or for persistent LB after antibiotic treatment. Conclusions: Our findings highlight the need for larger evaluations of laboratory tests using clinical samples from well-defined cases taken at different time-points during the course of the diseases. Since the diseases occur at a relatively low frequency, single-center cross-sectional studies are practically not feasible, but multi-center case control studies could be a way forward.